Expression and regulation of α‐transducin in the pig gastrointestinal tract. Issue 4 (18th February 2013) - Mazzoni, Maurizio; De, Roberto; Latorre, Rocco; Vallorani, Claudia; Bosi, Paolo; Trevisi, Paolo; Barbara, Giovanni; Stanghellini, Vincenzo; Corinaldesi, Roberto; Forni, Monica; Faussone‐Pellegrini, Maria S.; Sternini, Catia; et al.
Abstract Taste signalling molecules are found in the gastrointestinal (GI) tract suggesting that they participate to chemosensing. We tested whether fasting and refeeding affect the expression of the taste signalling molecule, α‐transducin (Gαtran), throughout the pig GI tract and the peptide content of Gαtran cells. The highest density of Gαtran‐immunoreactive (IR) cells was in the pylorus, followed by the cardiac mucosa, duodenum, rectum, descending colon, jejunum, caecum, ascending colon and ileum. Most Gαtran‐IR cells contained chromogranin A. In the stomach, many Gαtran‐IR cells contained ghrelin, whereas in the upper small intestine many were gastrin/cholecystokinin‐IR and a few somatostatin‐IR. Gαtran‐IR and Gαgust‐IR colocalized in some cells. Fasting (24 h) resulted in a significant decrease in Gαtran‐IR cells in the cardiac mucosa (29.3 ± 0.8 versus 64.8 ± 1.3, P < 0.05), pylorus (98.8 ± 1.7 versus 190.8 ± 1.9, P < 0.0 l), caecum (8 ± 0.01 versus 15.5 ± 0.5, P < 0.01), descending colon (17.8 ± 0.3 versus 23 ± 0.6, P < 0.05) and rectum (15.3 ± 0.3 versus 27.5 ± 0.7, P < 0.05). Refeeding restored the control level of Gαtran‐IR cells in the cardiac mucosa. In contrast, in the duodenum and jejunum, Gαtran‐IR cells were significantly reduced after refeeding, whereas Gαtran‐IR cells density in the ileum was not changed by fasting/refeeding. These findings provide further support to the concept that taste receptors contribute to luminal chemosensing in the GI tract and suggest they are involved in modulation of food intake and GI function induced by feeding and fasting.